Do Auctions and Forced Divestitures increase Competition? - Adriaan R. Soetevent; Marco A. Haan; Pim Heijnen (Tinbergen Institute, 2008)
Where markets are insufficiently competitive, governments can intervene by auctioninglicenses to operate or by forcing divestitures. The Dutch government has doneexactly that, organizing auctions to redistribute tenancy rights for highway gasolinestations and forcing the divestiture of outlets of four majors. We evaluate this policyexperiment using panel data containing detailed price information. We find that anobligation to divest lowers prices by over 2% while the auctioning of licenses withoutsuch an obligation has no discernible effect. We find weak evidence for price effects onnearby competitors.
Keywords: D43; D44; L11; 330; Divestitures; Auctions; Entry; Policy Evaluation; Auktion; Lizenz; Tankstelle; Autobahn; Markteintritt; Unvollkommener Wettbewerb; Wirkungsanalyse; Niederlande